2004
DOI: 10.1248/bpb.27.1275
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis X-Carboxymethylpullulan Conjugate: A Novel Homing Device to Spleen and Lymph Nodes

Abstract: We have previously found that carboxymethylpullulan (CMPul) conjugated with sialyl Lewis X (Neu5Aca a2-3Galb b1-4(Fuca a1-3)GlcNAc-, 2-3SLe x ) preferentially accumulates in the lymph nodes and spleen. In the present study, we investigated the structural requirements of the 2-3SLex moiety for this accumulation using rats. Radiolabeled CMPul conjugates with various degrees of substitution (d.s.) of the 2-3SLex moiety were intravenously administered to rats, and their tissue distributions were monitored by radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These findings are consistent with results of a study reporting that systemically administered NSCs tend to accumulate in the brains of mice with EAE, and also in the spleen and the liver (Politi et al 2007). E-selectin expression in the spleen has been described in humans, non-human primates and rodents (Redl et al 1991;Drake et al 1993;Schweitzer et al 1996;Alam et al 2000), and is upregulated by pro-inflammatory cytokines that are characteristically expressed in CNS inflammatory conditions (Weishaupt et al 2000;Emamgholipour et al 2013); indeed, conjugation of sLe x to polymers has been shown to markedly enhance the accumulation of such polymers within the spleen (Horie et al 2000(Horie et al , 2004, providing direct evidence that sLe x expression promotes splenic delivery. It has been reported that infiltration of the spleen by NSCs dampens production of inflammatory cytokines by resident spleen cells (e.g., macrophages) resulting in anti-inflammatory effects (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with results of a study reporting that systemically administered NSCs tend to accumulate in the brains of mice with EAE, and also in the spleen and the liver (Politi et al 2007). E-selectin expression in the spleen has been described in humans, non-human primates and rodents (Redl et al 1991;Drake et al 1993;Schweitzer et al 1996;Alam et al 2000), and is upregulated by pro-inflammatory cytokines that are characteristically expressed in CNS inflammatory conditions (Weishaupt et al 2000;Emamgholipour et al 2013); indeed, conjugation of sLe x to polymers has been shown to markedly enhance the accumulation of such polymers within the spleen (Horie et al 2000(Horie et al , 2004, providing direct evidence that sLe x expression promotes splenic delivery. It has been reported that infiltration of the spleen by NSCs dampens production of inflammatory cytokines by resident spleen cells (e.g., macrophages) resulting in anti-inflammatory effects (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%